2013
DOI: 10.1007/s11104-013-1621-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of two root systems, earthworms and mycorrhizae on the physical properties of an unstable silt loam Luvisol and plant production

Abstract: Background and aims Soil organisms are known to engineer the soil physical properties, but their impact is difficult to assess and poorly documented. Shrinkage analysis has a good potential for such assessment. This study analyses the effects of mycorrhizae (Glomus intraradices), earthworms (Allolobophora chlorotica) and two plants, Allium porrum (leek) and Petunia hybrida (petunia), on the physical properties of an unstable loamy Luvisol, as well as the biological interactions between the soil organisms. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 45 publications
(71 reference statements)
1
19
1
Order By: Relevance
“…In our case, we also found that the percentage of water-stable aggregates (WSA) at sizes of 2.00-1.00 and 1.00-0.50 mm was significantly higher in the mycorrhizal treatment as compared to non-mycorrhizal treatment (Table S1). Thus, the mycorrhizal hyphae entangle the soil particles and stabilize the macroaggregates [84] and the GRSPs help in the binding of these macroaggregates [85].…”
Section: Discussionmentioning
confidence: 99%
“…In our case, we also found that the percentage of water-stable aggregates (WSA) at sizes of 2.00-1.00 and 1.00-0.50 mm was significantly higher in the mycorrhizal treatment as compared to non-mycorrhizal treatment (Table S1). Thus, the mycorrhizal hyphae entangle the soil particles and stabilize the macroaggregates [84] and the GRSPs help in the binding of these macroaggregates [85].…”
Section: Discussionmentioning
confidence: 99%
“…Greater root systems could provide more chances to be colonized by AMF, thereby increasing the production of hyphae, finally more GRSP production. On the other hand, a better root system could also release more root exudates into the rhizosphere16, which could directly affect aggregate stability. However, no information is available if a direct effect of roots on aggregate stability in a larger growth container could be stronger than that of mycorrhizal hyphae.…”
Section: Discussionmentioning
confidence: 99%
“…The ubiquitous soil arbuscular mycorrhizal fungi (AMF) can contribute to soil aggregate stability directly by their extraradical fungal hyphae1131415 or indirectly by altering the biochemical and morphological properties of host plants2. Such direct and indirect contributions are often intertwined together16. For instance, a microcosm experiment showed that mean weight diameter (MWD, an indicator of aggregate stability) highly positively correlated with soil hyphal length but weakly with root volumes13.…”
mentioning
confidence: 99%
“…Plant-soil surface structure interactions are proper feedback process: Plant canopies and/or residues from previous crops reduce runoff and evaporation and thereby enhance further plant growth due to better water availability. Plant effects on surface soil structure are related to the protective canopy effect against aggregate slaking (Zuazo and Pleguezuelo 2008), root/mycorrhiza enmeshment of (macro)aggregates (Gyssels et al 2005;Kohler-Milleret et al 2013), more active soil macrofauna (Facelli and Pickett 1991;Lavelle et al 2006), enhanced microbial activity in shaded soil due to less extreme temperatures and reduced ultraviolet radiation (Hatfield and Pruegar 1996;Zogg et al 1997;Ballaré et al 2011) and lower coalescence due to less drying of soil under canopy/mulch coverage (Mulumba and Lal 2008).…”
Section: Subsystem Interactions and Feedbacksmentioning
confidence: 99%